Numerical optimization - Nocedal, Jorge (Springer, 2015)
'Numerical Optimization' presents a comprehensive description of the effective methods in continuous optimization. The book includes chapters on nonlinear interior methods & derivative-free methods for optimization. It is useful for graduate students, researchers and practitioners.